Telephone counseling for young Brazilian cocaine and/or crack users. Who are these users? - Nadia K. Bisch; Taís de C. Moreira; Mariana C. Benchaya; Dan R. Pozza; Larissa C. N. de Freitas; Michelle S. Farias; Maristela Ferigolo; Helena M.T. Barros (Brazilian Society of Pediatrics, 2019)
Objective: To describe the users' drug abuse characteristics, problematic behaviors associated with addiction, the motivation of teenagers and young adults to quit cocaine and/or crack abuse, and then compare these characteristics. Methods: A cross‐section study was conducted with 2390 cocaine/crack users (teenagers from 14 to 19 years of age, and young adults from 20 to 24 years of age); 1471 were young adults and 919 were teenagers who had called a phone counseling service between January 2006 and December 2013. Semi‐structured interviews were performed via phone calls. The questionnaires included sociodemographic information; assessment of the characteristics of cocaine/crack abuse; assessment of the problematic behaviors; also, the Contemplation Ladder was used to evaluate the stages of readiness to cease substance abuse. Results: Participants reported using cocaine (48.2%), crack and other smoking forms (36.7%) and combined consumption of both drugs (15%). Young adults were more prone to using crack or crack associated with cocaine (OR = 1.9; CI 95% = 1.05-1.57) and they were exposed to substance abuse for longer than two years (OR = 3.45; CI 95% = 2.84-4.18), when compared to teenagers. On the other hand, they showed higher readiness to quit. Conclusion: Data shows important differences in drug abuse characteristics, problematic behaviors and motivation to cease substance abuse between teenager and young adult cocaine and/or crack users. Behaviors displayed by young adults involve greater physical, mental and social health damages. These findings reinforce the importance of public policy to act on prevention and promoting health, to increase protection factors among teenagers and lower risks and losses during adult life. Resumo: Objetivo: Descrever as características de consumo, comportamentos problemáticos associados ao uso e motivação para cessar o consumo entre adolescentes e jovens usuários de cocaína e/ou crack e comparar essas características. Métodos: Realizou-se um estudo transversal, com 2.390 usuários de cocaína/crack (adolescentes: 14 - 19 anos e jovens: 20 - 24 24 anos) sendo 1471 jovens e 919 adolescentes, que ligaram para um serviço de aconselhamento telefônico entre janeiro de 2006 e dezembro de 2013. Foram realizadas entrevistas semiestruturadas por telefone. Os questionários incluíram informações sociodemográficas; avaliação das características do consumo de cocaína/crack; avaliação dos comportamentos problemáticos e escala de Contemplação Ladder para avaliar os estágios de motivação. Resultados: Os participantes relataram uso de cocaína (48,2%), crack e outras formas fumadas (36,7%) e uso associado de ambas as formas (15%). Os jovens faziam maior uso de crack ou crack associado à cocaína (OR = 1,19; IC 95% = 1,05‐1,57) e estavam expostos ao uso da droga havia mais de 2 anos (OR = 3,45; IC 95% = 2,84‐4,18) quando comparados aos adolescentes. Por outro lado, mostraram‐se mais motivados para cessar o consumo. Conclusão: Os dados mostraram haver importantes diferenças nas características de consumo, comportamentos problemáticos e motivação para cessar o consumo entre adolescentes e jovens usuários de cocaína e/ou crack. Os jovens apresentaram comportamentos que envolvem maiores prejuízos para a saúde física, mental e aspectos sociais. Esses achados reforçam a importância de ações de políticas públicas de prevenção e promoção de saúde para aumentar os fatores de proteção entre os adolescentes e reduzir riscos e prejuízos para a vida adulta. Keywords: Telephone counseling, Drug addiction, Youth, Teenagers, Cocaine, Crack, Palavras‐chave: Aconselhamento telefônico, Dependência química, Jovens, Adolescentes, Cocaína, Crack